Associations Between Clinical Manifestations and the Final Status COVID-19 Sufferer in Palembang, Indonesia - Prastykha Tri Wahyuni; Najmah Najmah; Citra Afny Sucirahayu; Azmiyah Rahma Zanjabila; Silvy Alvionita; Fenty Aprina; Yudhi Setiawan (Faculty of Public Health, Sriwijaya University, 2022)
The clinical manifestations of COVID-19 are the developments and impacts caused by COVID-19. Each person's clinical manifestations vary, such as mild and severe stages. The elderly and pre-elderly as a risk group usually experience severe clinical manifestations. As a result, they have a higher fatality rate than other groups with the highest mortality cases in Palembang City. This study aims to determine the associations between clinical manifestations and final status in the elderly and pre-elderly aged 50 with COVID-19 in Palembang City. This study uses a descriptive-analytic, cross-sectional research design by analyzing secondary data Epidemiological Surveillance Information System (SISUGI) COVID-19. The research sample was 278 data on elderly and pre-elderly with COVID-19 aged 50 in Palembang City who met the inclusion criteria. Data analysis techniques were univariate, bivariate, and multivariate. Univariate results were that 14.7% of elderly and pre-elderly died, and 37.4% experienced severe clinical manifestations. Bivariate analysis showed significant associations (p < 0.0001) between clinical manifestations and the last level of the elderly and pre-elderly with COVID-19 in Palembang City (OR: 3.982; CI 95%: 1.977-8.024). There are associations between clinical manifestations and final status after controlling for variables of occupation, age, and history of comorbidities. The comorbid history variable was found as the confounding variable. The research hopes to become the basis for categorizing the clinical manifestations of COVID-19 to prevent poor final status, especially in the elderly and pre-elderly groups